A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages MINISTRY OF HEALTH AND DEPARTMENT OF HEALTH FOR SCOTLAND A National Health Service THE WHITE PAPER PROPOSALS IN BRIEF NOTE: This is an official abridged version of the Government's proposals in their White Paper on a National Health Service. Every effort has been made to avoid discrepancies of terms or substance betwen this and the White Paper itself. If, however, any uncertainty arises, it is to the White Paper that the reader must look for explanation. LONDON: HIS MAJESTY'S STATIONERY OFFICE: 1944 THREEPENCE NET 36/H24/41